Midlife hypertension is a risk factor for some, but not all, domains of cognitive decline in later life: a systematic review and meta-analysis - Mockler, David; Kelly, Aine; Wilson, Fiona (Ovid Technologies (Wolters Kluwer Health), 2023)
Midlife hypertension is a risk factor for some, but not all, domains of cognitive decline in later life: a systematic review and meta-analysis Ois ın Cormac Joyce a , Cl ıodhna McHugh a , David Mockler b , Fiona Wilson c , and Aine M. Kelly a Introduction: Management of midlife blood pressure and hypertension status may provide a window of intervention to mitigate cognitive decline with advancing age. The aim of this review was to investigate the relationship between midlife hypertension and cognition in midlife and later life. Methods: Online electronic databases were searched from their inception to May 2022. Studies assessing midlife (40– 65 years) hypertension and cognition at mid and/or later- life were included. A random effects meta-analysis was deemed appropriate. Results: One hundred forty-nine studies across 26 countries were included. Qualitative synthesis found negative relationships between midlife hypertension and later life cognition in the domains of memory, executive function, and global cognition. Metanalytical evidence revealed midlife hypertension negatively impacts memory, executive function, and global cognition but had no observed effect on attention at midlife. Discussion: Hypertension at midlife has a significant negative impact on cognition in mid-life and later life, namely memory, executive function, and global cognition.
PUBLISHED
Keywords: cognition, high blood pressure, hypertension, middle-aged, midlife